Web-Based Village Population Data Management System - Turino, Sebastianus Handri; Adisusilo, Anang Kukuh (IC-ITECHS, 2024)
Village Government is one of the governments in charge of organizing and managing resources in government at the Village level and has the obligation to administer population data. Currently, the Coal Village office is still handling the population data administration process manually. The system is still manual and uses Microsoft Word and Microsoft Excel, of course there are still many errors or shortcomings in the data processing process, which can slow down the process of adding data, searching for data and storing data. Apart from that, archiving files is less organized so it will make it difficult to find data. In an effort to overcome the problems above, a new website-based system is needed that will help management speed up and accurate population data. This computerized system will eliminate file accumulation. To achieve the objectives outlined above, this was done by conducting observations through interviews with the Village government to obtain needs for problems that often occur when managing population data. What is then carried out is system analysis, identifying user needs, process mapping, identifying frequently occurring problems, mapping system requirements so that it is hoped that the implementation of the right solution can be realized according to user needs. In an effort to overcome the problems above, a new website-based system is needed which will assist Village management in speed and accuracy of population data. With this population data processing information system, satisfaction in the service process can not only be felt by the community who act as customers, but can also be felt by all staff at the Coal Village Office because the recording and storage process becomes easier to manage.